Investigation of the possible applications for microtextured rolling bearings - Kelley, Josephine; Poll, Gerhard; Pape, Florian (Frontiers in Manufacturing Technology, 2022)
The application of microdimple textured surfaces for rolling bearings is not very common but can be beneficial for various usage scenarios. In contrast to the applications for plain bearings or cylinder running surfaces, however, surface patterns for rolling bearings only offer advantages under certain conditions. For example, for use with start-stop cycles, in mixed lubrication conditions or under sliding conditions in a bearing as well as on a roller - bearing flange contact, friction can be reduced with the targeted use of microdimples. The geometry of the microdimples must be chosen so that the dimple fit in the contact area between the ball or roll and the bearing surface in order to act as a reservoir for the lubricant. First applications for a microdimple textured angular contact ball bearing under oscillating movement conditions and for tapered roller bearings are discussed. By means of a calculation approach, the behavior for microstructured tapered roller bearings is considered.